PENGGUNAAN MEDIA POWER POINT UNTUK MENINGKATKAN MOTIVASI DAN PRESTASI BELAJAR FISIKA SISWA KELAS X MIPA 2 SMA NEGERI 1 KERAMBITAN - Suadnyana, I Made (Widyadari : Jurnal Pendidikan, 2019)
The purpose of the research is (1) to increase students learning motivation in the process of teaching by using power point. (2) to increase Fisika learning achievement of the class X MIPA 2 SMA Negeri 1 Kerambitan in the teaching learning process using power point media. Based on the result of the research in USA, teaching learning process by using the help of media can increase efficiency 47% and with the help of ICT can increase 93%. The subject of the researh is the students of X MIPA 2 class of SMA Negeri 1 Kerambitan with 39 students consists of 16 boys and 23 girls with the object of research is students motivation during the process of teaching learning using power point media. Motivation is measured by indicating student activity in following teaching learning process in the class room or outside class room. Technique of collecting data using questionaire, sheet observation, the result of daily test document. To process the data by using descriptive analysis. The result of the research indicates that active participation of the students learning in the class from earlier the first cycle to the second cycle can increase the students activity learning. Most of the students do the exercises deligently, the task that given from the teacher or from their own choice. The encreasing of the average procentace of the students in doing exercises is 20,49%, the eagerness of asking to the teacher or their friends increases 30,80% and the aegerness to give response to the problem proposed by their friends or the teacher is increasing 10,69 %. The average achievement of students daily test is increasing 12,70 %, the average deviation from creterian minimal learning target (KKM) is increasing 12.70 %, learning acheivement (daya serap) is increasing 12.70%, learning target (daya ketuntasan) is increasing 28,21 %, the bight score is increasing 3 and the lowest score is increasing 27.